Low GRK2 Underlies Hyperalgesic Priming by Glial Cell-Derived Neurotrophic Factor - Wang, Hui-Jing; Gu, Han-Xin; Eijkelkamp, Niels; Heijnen, Cobi J.; Kavelaars, Annemieke (Frontiers in Pharmacology, 2018)
Background: We recently identified the balance between the level of G protein coupled receptor kinase 2 (GRK2) and Epac1 in nociceptors as a key factor in the transition from acute to chronic pain that occurs in mice ‘primed’by an inflammatory stimulus. Here we examined the contribution of GRK2 and Epac-signaling to growth factor-induced hyperalgesic priming. Methods:Mice were primed by intraplantar injection with Glial cell-derived neurotrophic factor (GDNF). Mechanical allodynia in response to PGE2 was followed over time in primed and non-primed animals. GRK2 protein levels in dorsal root ganglion (DRG) neurons were quantified by immunohistochemistry. The effect of HSV-GRK2 amplicons to restore GRK2 levels or of an Epac inhibitor on PGE2 allodynia in primed mice was examined.Results: GDNF-induced hyperalgesia disappeared within 12 days. The hyperalgesic response to a subsequent intraplantar injection of PGE2 was prolonged from <24 h in control mice to more than 72 h in GDNF-primed mice.In male and female primed mice, PGE2 hyperalgesia was inhibited by oral administration of the Epac inhibitor ESI-09, while the drug had no effect in control mice. Mice primed with GDNF had reduced levels of GRK2 in IB4(+) small DRG neurons, but normal GRK2 levels in IB4(-) DRG neurons. Intraplantar administration of HSV-GRK2 amplicons to increase GRK2 protein levels prevented the prolongation of PGE2-induced hyperalgesia in GDNF-primed mice. Conclusion: Low GRK2 in nociceptors is critical to develop a primed state in response to GDNF and leads to engagement of Epac signaling and transition to chronic PGE2-induced hyperalgesia. Increasing GRK2 protein or inhibiting Epac signaling may represent new avenues for preventing transition to a chronic pain state.